2012
DOI: 10.1080/00268976.2012.689868
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between polar molecules subject to a far-off-resonant optical field: entangled dipoles up- or down-holding each other

Abstract: We show that the electric dipole–dipole interaction between a pair of polar molecules undergoes an all-out transformation when superimposed by a far-off-resonant optical field. The combined interaction potential becomes tunable by variation of wavelength, polarisation and intensity of the optical field and its dependence on the intermolecular separation exhibits a crossover from an inverse-power to an oscillating behaviour. The ability thereby offered to control molecular interactions opens up avenues toward t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Chemical reactions in such a gas are determined by the rate of tunneling through the long-range barriers [710], which as shown earlier by Bohn and coworkers, is sensitive to external fields. Even more effectively, the long-range repulsive barriers can also be created by dressing molecules with a combination of dc electric and microwave fields [107,108], and far-off resonant laser fields [95,109]. As was shown in refs.…”
Section: B Towards Controlled Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical reactions in such a gas are determined by the rate of tunneling through the long-range barriers [710], which as shown earlier by Bohn and coworkers, is sensitive to external fields. Even more effectively, the long-range repulsive barriers can also be created by dressing molecules with a combination of dc electric and microwave fields [107,108], and far-off resonant laser fields [95,109]. As was shown in refs.…”
Section: B Towards Controlled Chemistrymentioning
confidence: 99%
“…Entanglement can be found in strongly interacting atomic and molecular gases, however it is challenging to generate highly entangled states between weakly interacting particles in a scalable way. Based on the work of Lemeshko and Friedrich [95,109], Herrera et al [808] recently described a one-step method to generate entanglement between polar molecules in the absence of dc electric fields. They showed that alignment-mediated entanglement in a molecular array is long-lived and discussed applications for quantum information processing and quantum metrology.…”
Section: Entanglement Of Molecules and Dipole Arraysmentioning
confidence: 99%
“…Furthermore, the phenomenon is expected to occur for other types of anisotropic interparticle interactions, such as quadrupole-quadrupole couplings 113,114 or interactions induced by far-off-resonant laser fields 115,116 . We use the dual boson formalism to strongly correlated systems 79,80 .…”
Section: Discussionmentioning
confidence: 99%
“…The most familiar intrinsic forces of this inter-particle type are the well-known field-independent Casimir-Polder interactions, 5-10 which relate to the van der Waals or dispersion interaction, first characterized in London's calculation (which derived an R -6 dependence): Casimir and Polder's more accurate derivation, based on quantum electrodynamics (QED), revealed an R -7 dependence in the long-range. However, on the presence of a laser beam of sufficient intensity, the form and magnitude of the inter-particle coupling forces may be modified through a phenomenon known as optical binding, [11][12][13][14][15][16][17][18][19] which may override the intrinsic force. Despite a diverse set of optical processes being operational for particle sizes approaching or exceeding the wavelength of the throughput beam, the case of non-contact interactions between 'Rayleigh particles' has a specifically QED origin.…”
Section: Introductionmentioning
confidence: 99%